Epstein–Barr virus antibodies mark systemic lupus erythematosus and scleroderma patients negative for anti‐DNA. Issue 2 (February 2014) - Fattal, Ittai; Shental, Noam; Molad, Yair; Gabrielli, Armando; Pokroy‐Shapira, Elisheva; Oren, Shirly; Livneh, Avi; Langevitz, Pnina; Pauzner, Rachel; Sarig, Ofer; Gafter, Uzi; Domany, Eytan; et al.
Summary Systemic lupus erythematosus (SLE) is an autoimmune disease that can attack many different body organs; the triggering event is unknown. SLE has been associated with more than 100 different autoantibody reactivities – anti‐dsDNA is prominent. Nevertheless, autoantibodies to dsDNA occur in only two‐thirds of SLE patients. We previously reported the use of an antigen microarray to characterize SLE serology. We now report the results of an expanded study of serology in SLE patients and scleroderma (SSc) patients compared with healthy controls. The analysis validated and extended previous findings: two‐thirds of SLE patients reacted to a large spectrum of self‐molecules that overlapped with their reactivity to dsDNA; moreover, some SLE patients manifested a deficiency of natural IgM autoantibodies. Most significant was the finding that many SLE patients who were negative for autoantibodies to dsDNA manifested abnormal antibody responses to Epstein–Barr virus (EBV): these subjects made IgG antibodies to EBV antigens to which healthy subjects did not respond or they failed to make antibodies to EBV antigens to which healthy subjects did respond. This observation suggests that SLE may be associated with a defective immune response to EBV. The SSc patients shared many of these serological abnormalities with SLE patients, but differed from them in increased IgG autoantibodies to topoisomerase and centromere B; 84% of SLE patients and 58% of SSc patients could be detected by their abnormal antibodies to EBV. Hence an aberrant immune response to a ubiquitous viral infection such as EBV might set the stage for an autoimmune disease.